Measures for the formation of a healthy lifestyle - To'lanov Mamasidiq Qodirovich (Western European Studies, 2023)
This article explores the multifaceted aspects of forming and maintaining a healthy lifestyle. Drawing upon existing literature, the study analyzes various measures, including physical activity, nutrition, mental health, sleep hygiene, and stress management. The research employs a comprehensive approach to investigate the impact of these measures on overall well-being. Results indicate that integrating these practices can significantly contribute to the development of a sustainable and healthy lifestyle.
Keywords: Healthy lifestyle; wellness; physical activity